2020
DOI: 10.1001/jama.2020.15779
|View full text |Cite
|
Sign up to set email alerts
|

Otolaryngology–Head and Neck Surgery and COVID-19

Abstract: The novel coronavirus disease 2019 (COVID-19) pandemic has had a particularly large influence on the specialty of otolaryngology-head and neck surgery. Molecularstudiesimplicatenasalepithelialcells,specificallygoblet and ciliated cells, as the entry site for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and a reservoir for dissemination within a given patient and from person to person. The development of acute loss of smell and taste was quickly recognized as one of the symptoms of COVID-19. 1 T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 10 publications
0
25
0
Order By: Relevance
“…Thus, SLPs in a number of different settings were deemed appropriate including those in acute care, outpatient clinics, rehabilitation centers, skilled nursing facilities (SNFs), home health, among others. Our justification for targeting this SLP participant population was that these clinicians were likely to be engaged in performing clinical procedures that may be considered high risk in terms of COVID-19 exposure and transmission (Piccirillo, 2020) such as TEP voice prosthesis changes, endoscopic exams for voice and swallowing, and dysphagia evaluations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, SLPs in a number of different settings were deemed appropriate including those in acute care, outpatient clinics, rehabilitation centers, skilled nursing facilities (SNFs), home health, among others. Our justification for targeting this SLP participant population was that these clinicians were likely to be engaged in performing clinical procedures that may be considered high risk in terms of COVID-19 exposure and transmission (Piccirillo, 2020) such as TEP voice prosthesis changes, endoscopic exams for voice and swallowing, and dysphagia evaluations.…”
Section: Methodsmentioning
confidence: 99%
“…Transmission of COVID-19 is of particular relevance to those professionals whose potential risk is higher because they perform aerosol generating procedures (AGPs) such as endoscopic evaluations for voice and swallowing. An AGP is defined as any procedure that has the potential to produce aerosols and droplets of varying sizes (Jackson et al 2020;Piccirillo, 2020;Zaga et al, 2020). A recent report has explicitly outlined the increased risk of death by physicians in relation to COVID-19 (Ing et al, 2020).…”
mentioning
confidence: 99%
“…[5][6][7][8] Within otolaryngology, subspecialties vary in their elective nature as well as the risk of COVID-19 exposure, with rhinology and head and neck surgery at highest risk. 5 Nasal and transnasal endoscopic procedures are among the highest-risk procedures in otolaryngology, whereas the risk for transmission in head and neck surgery procedures is directly proportional to the degree of mucosal exposure; thus, neck and thyroid surgery tends to be of lower transmission risk as compared with transoral procedures. 6 Various otolaryngologyrelated tiering systems were consequently developed at hospitals across the world, including Thomas Jefferson University, to decrease nosocomial COVID-19 transmission to patients and providers while providing timely care.…”
mentioning
confidence: 99%
“… 3 , 4 Otolaryngology was deemed to be a high-risk specialty for COVID-19 transmission due to its primary focus on the nasopharynx and respiratory tract and to the substantial aerosol production during operative procedures. 5 - 7 Numerous studies have indicated the localization of large viral loads in the nasal epithelial cells, with the nasal cavity and nasopharynx having the highest concentrations of virus in the upper respiratory tract. 5 - 7 These factors, in combination with reports of inadequate personal protective equipment and delayed turnaround time for diagnostic testing, placed otolaryngology providers at high risk during surgical procedures in the early stages of the pandemic.…”
mentioning
confidence: 99%
See 1 more Smart Citation